2019
DOI: 10.1139/cjp-2018-0551
|View full text |Cite
|
Sign up to set email alerts
|

Study of Al2O3/copper–water nanoparticle shape, slip effects, and heat transfer on steady physiological delivery of MHD hybrid nanofluid

Abstract: This paper contains the analytical investigation of magnetohydrodynamic (MHD) flow of copper/Al2O3–water hybrid nanofluid with unstable peristaltic motion. Three different geometries (bricks, cylinder, and platelets) along with velocity and thermal slip conditions are studied in detail to reach the precise solution. Flow geometry of a non-uniform tube of finite length, experimental values of base fluid, and considered nanoparticles are taken into account to examine the theoretical investigation of formulated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The MHD flow of a hybrid nanofluid in the presence of the slip condition was considered by Nadeem and Abbas [51], and they adopted the thermophysical properties of Devi and Devi [23,24] to solve the system of ordinary differential equations (ODEs). Using the same properties, Iftikhar et al [52] also investigated the steady MHD flow of hybrid nanofluid with the slip condition. Based on published literature, it can be concluded that the thermophysical properties of Devi and Devi have been used broadly, as these properties match with the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…The MHD flow of a hybrid nanofluid in the presence of the slip condition was considered by Nadeem and Abbas [51], and they adopted the thermophysical properties of Devi and Devi [23,24] to solve the system of ordinary differential equations (ODEs). Using the same properties, Iftikhar et al [52] also investigated the steady MHD flow of hybrid nanofluid with the slip condition. Based on published literature, it can be concluded that the thermophysical properties of Devi and Devi have been used broadly, as these properties match with the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…From Figure 1 it is observed that the convergence region decreases with the increasing deviation of ε from 1. The convergence region for shrinking sheet case with 0.25 From these plots it is observed that with increase in both Pr and λ the convergence region decreases [36][37][38][39][40][41]. The influence of different involved parameters over velocity and temperature profiles is sketched in Figures 4-7.…”
Section: Resultsmentioning
confidence: 99%
“…The acquire pair of non-linear partial differential equations is transformed from similarity transformation into ODEs along with suitable boundary conditions is numerically solved with help shooting technique by the assistance of Runge-Kutta method [35][36][37]. Now implementing shooting method iterative process in MATLAB coding to approach the approximate solution and based on that we work out for satisfactory IVP that gives the appropriate answer of solution for initially determine BVP for the fluid model and discuss the solution with help of graphical representation and tabular form [38][39][40].…”
Section: Resultsmentioning
confidence: 99%